Re-engineering Trane automated test utility - Wilson, Kevin (My University, 2010)
Automated testing accounts for a large portion of the controls testing process at the Trane Company. The Trane Automated Test Utility (TATU) is a software tool that is responsible for handling the automated test procedures using a keyword based language. Because the features of the controls products are constantly changing, maintaining the testing tool to support new products is difficult and can cause delays in the testing phase of product development. This manuscript describes a tool that enhances TATU by dynamically adding keywords to the testing language. In doing so, test teams have the ability to support their testing process internally and do not have to rely on TATU developers to implement new keywords. While this tool does not support execution of tests or many of the other features TATU has to offer, it is an important part of a much larger project to develop a new version of TATU.
Keywords: Application software -- Development.; Air conditioning -- Testing.; Automatic test equipment.; Trane Company.